Variable friction damped self-centering precast concrete beam–column connections with hidden corbels: Experimental investigation and theoretical analysis. (1st March 2020) - Huang, Linjie; Zhou, Zhen; Huang, Xiaogang; Wang, Yongwei
Highlights: Variable friction dampers are incorporated with post-tensioning technology. Shear capacity of connection is provided by friction and hidden corbels. A novel flag-shape hysteretic curve is proposed. Post-decompression stiffness and energy dissipation are increased. Abstract: A new self-centering precast concrete (SCPC) beam–column connection with variable friction dampers (VFDs) is proposed to enhance the stiffness and energy dissipation after gap opening occurs at the beam–column interface, where a hidden corbel (HC) is placed to increase the vertical shear capacity and construction efficiency. Especially, the VFDs are composed of grooved steel plates instead of the flat steel plates used in most common friction dampers, which enhances the flexibility of seismic design. Applying grooved steel plates with different geometric characteristics and adjusting the key design parameters including the initial post-tensioned (PT) forces, pre-stressing clamping forces applied to friction bolts, and number of PT tendons, a series of tests was conducted on a full-scale beam–column specimen to investigate the hysteretic behavior of such HC–VFD–SCPC beam–column connections. Incorporating the characteristics of twice activation for VFDs with the different seismic requirements for various seismic levels, the theoretical basis was proposed and some recommendations were obtained for the seismic design of structures containing such beam–column connections. The experimental and theoretical results show that the arrangement of these VFDs in the beam–column connection achieved the expected self-centering capacity and hysteretic behavior of variable stiffness and energy dissipation after gap opening occurred at the beam–column connection. The hysteretic behavior of variable stiffness and energy dissipation is observed to be sensitive to the details of the VFDs, initial force, number of PT tendons, and pre-stressing clamping forces applied to friction forces.